ISLAM UNDER THE PALESTINE MANDATE : Colonialism and the Supreme Muslim Council - Roberts, Nicholas E., author (London ; New York : I.B. Tauris & Co. Ltd, 2017)
Concerns about the place of Islam in Palestinian politics are familiar to those studying the history of the modern Middle East. A vital part of this history is the rise of Islamic opposition to the British in Mandate Palestine during the 1920s and 30s. Colonial officials had wrestled with the question of how to rule over a Muslim-majority country and considered traditional Islamic institutions essential for maintaining order. Islam under the Palestine Mandate tells the story of the search for a viable Islamic institution in Palestine and the subsequent invention of the Supreme Muslim Council. As a body with political recognition, institutional autonomy and financial power, the council was intended to act as a counterweight to the growing popularity of nationalism among Palestinians. However, rather than diminishing the revolutionary capacity of the colonized, the council became one of the most significant of the opposition groups to British rule, especially under its highly controversial president, the Grand Mufti of Jerusalem, Hajj Amin al-Husayni. Making extensive use of primary sources from British and Israeli archives, this book offers an account of the establishment of the Supreme Muslim Council and the policing of Arab nationalist sympathizers. Roberts argues against the view that the council's creation was an act of appeasement towards Muslim opinion, showing how British actions were guided by techniques of imperial administration used elsewhere in the empire